Is Post-Fukushima Reform Making Japan Safer? From Shared Responsibility to Collective Accountability - Takao, Yasuo (Taylor & Francis, 2023)
Ten years after the Fukushima disaster, the nuclear safety regulation system in Japan has gradually moved from the exclusionary process of policy making, based on hierarchically organized policy, to a decentralized and open process of policy making whose competence is divided beyond the pre-given political actors. Yet policy making and implementation need to bring together multiple stakeholders to work in concert to achieve a desired outcome of nuclear safety. This article seeks to explain why the trend towards more inclusive forms of policy making may still lead to negative consequences for democratic accountability of nuclear safety. The author argues that the coordination issue becomes critical to a plurality of conflicting interests and beliefs of autonomous stakeholders. Although the decision-making plurality favours democratic interest representation, empirical evidence suggests that a poorly coordinated response by the national government to nuclear policy implementation fails to get stakeholders to work together for Japan’s nuclear safety. From a broader perspective, the lack of coordination among different stakeholders is one of the weaknesses of expanding accountability mechanisms to include more stakeholders, and results in challenges to policy coherence.